SARS-CoV-2 infection among healthcare workers in a hospital in Madrid, Spain. Issue 2 (October 2020) - Suárez-García, I.; Martínez de Aramayona López, M.J.; Sáez Vicente, A.; Lobo Abascal, P.
Summary: Background: Healthcare workers (HCWs) are especially vulnerable to infection by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Aim: The aim of this study was to describe the epidemiological and clinical characteristics of coronavirus disease 2019 (COVID-19) among HCWs from February 24 th to April 30 th, 2020, in a hospital in Madrid, Spain. Methods: This was a retrospective cohort study. Cumulative COVID-19 incidence was calculated for all HCWs and categorized according to presumed level of COVID-19 exposure (high, medium, and low). Findings: Among 1911 HCWs, 213 (11.1%) had COVID-19 during the study period. Cases increased gradually from March 8 th, peaking on March 17 th and declining thereafter. The peak of cases among HCWs was reached 14 days before the peak in admitted COVID-19 cases in the hospital. There were no significant differences in the proportion of COVID-19 cases according to level of occupational exposure ( P  = 0.123). There were five departments and two professions in which >20% of the workers had confirmed COVID-19. Temporal clusters were identified in three of these departments and one profession, with most of the cases occurring over a period of less than five days. The prevalence of comorbidities was low and 91.5% of patients had mild or moderate symptoms. Eleven patients were admitted to the hospital and one patient needed intensive care. None of the patients died. The median time of sick leave was 20 (interquartile range: 15–26) days. Conclusion: The results suggest that HCW–HCW transmission accounted for part of the cases. In spite of a low prevalence of comorbidities and a mild clinical course in most cases, COVID-19 caused long periods of sick leave.